Formation of an intramolecular triple-stranded DNA structure monitored by fluorescence of 2-aminopurine or 6-methylisoxanthopterin - Shchyolkina, Anna K. (Oxford University Press, 2004)
The parallel (recombination) ‘R-triplex’ can accommodate any nucleotide sequence with the two identical DNA strands in parallel orientation. We have studied oligonucleotides able to fold back into such a recombination-like structure. We show that the fluorescent base analogs 2-aminopurine (2AP) and 6-methylisoxanthopterin (6MI) can be used as structural probes for monitoring the integrity of the triple-stranded conformation and for deriving the thermodynamic characteristics of these structures. A single adenine or guanine base in the third strand of the triplex-forming and the control oligonucleotides, as well as in the double-stranded (ds) and single-stranded (ss) reference molecules, was substituted with 2AP or 6MI. The 2AP*(T·A) and 6MI*(C·G) triplets were monitored by their fluorescence emission and the thermal denaturation curves were analyzed with a quasi-two-state model. The fluorescence of 2AP introduced into an oligonucleotide sequence unable to form a triplex served as a negative control. We observed a remarkable similarity between the thermodynamic parameters derived from melting of the secondary structures monitored through absorption of all bases at 260 nm or from fluorescence of the single base analog. The similarity suggests that fluorescence of the 2AP and 6MI base analogs may be used to monitor the structural disposition of the third strand. We consider the data in the light of alternative ‘branch migration’ and ‘strand exchange’ structures and discuss why these are less likely than the R-type triplex.